Pengaruh Kepuasan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan pada PT Berkat Nirwana Teknik di Kabupaten Tangerang - Meilin Damaiana Sinaga; Suryanto Sosrowidigdo; Siti Nurjanah (International Forum of Researchers and Lecturers, 2026)
A company's success is largely determined by employee performance. This study examines the influence of job satisfaction and work motivation on employee performance, both partially and simultaneously, among employees at PT Berkat Nirwana Teknik in Tangerang Regency. A quantitative associative approach was applied to 50 employees using a saturated sampling technique. Data were collected through Likert-scale questionnaires and analyzed using SPSS version 27 through multiple linear regression, t-test, F-test, and coefficient of determination. The results show that job satisfaction does not have a statistically significant partial effect on employee performance (t = 1.521; sig. = 0.135), whereas work motivation has a positive and significant partial effect (t = 7.060; sig. = 0.001). Simultaneously, job satisfaction and work motivation have a significant effect on employee performance (F = 94.302; sig. = 0.001), with a coefficient of determination of 80.1%. These findings indicate that work motivation plays a more prominent role in improving employee performance, while job satisfaction remains an important supporting factor for long-term performance. Therefore, company management is encouraged to strengthen work motivation programs while maintaining efforts to support employee job satisfaction.